Education as a Means, Not End: Perspectives from Nepal (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The issue includes nine research articles from Nepali scholars who have explored the current status and key issues in Nepali higher education, seeking to offer broader perspectives. The articles have highlighted social disparities in the Nepali society reflected in its higher education, influence and domination of the western knowledge, professional development of teachers and shifting practices in teaching learning due to the recent global pandemic of Covid-19.